Asesor en derechos de autor: un nuevo rol del bibliotecario universitario? - Molina, Juan Carlos Fernandez; Vives-Gracia, Josep; Guimarães, José Augusto Chaves [UNESP] (My University, 2011)
Considering that university librarians have an advantageous position in mediating information resources and users, one can consider them as the more suitable professionals to provide intellectual property advice to professors and students. But, ¿do they really have the required knowledge to face that duty? To determine the level of knowledge, among university librarians, about copyright problems, a questionnaire was used to survey librarians of the University of Granada. The results show a considerable lack of knowledge what points out to the need of a training program about these issues as a priority matter for the current university libraries.

La privilegiada situación de los bibliotecarios como intermediarios entre las fuentes de información y los usuarios, les convierte en los profesionales más adecuados para proporcionar, tanto a profesores como estudiantes, unos servicios de valor añadido de asesoría y gestión de la propiedad intelectual. Pero, ¿tienen realmente los bibliotecarios los conocimientos necesarios para asumir tal función? Con el objetivo de averiguar el nivel de conocimientos de los bibliotecarios universitarios sobre las cuestiones básicas de los derechos de autor, se pasó un cuestionario a bibliotecarios de la Universidad de Granada. Los resultados ponen de manifiesto que sus conocimientos son insuficientes, por lo que un plan de formación sobre estas cuestiones debería ser una prioridad para las actuales bibliotecas universitarias.